Analysis of Community Empowerment Programs in the Suku Anak Dalam Community (Orang Rimba) at Talang Kejumat Settlement Location, Limbur Tembesi, Bathin VIII, Sarolangun Regency - Wilan Melia Ningsih; Iradhad Taqwa Sihidi (Budapest International Research and Critics University, 2022)
This study aims to determine the empowerment program carried out by stakeholders for the Suku Anak Dalam (SAD) community and to find out the obstacles in realizing the empowerment program for the Suku Anak Dalam (SAD) community. This study uses a qualitative research method with a source approach (Institutional Research) by describing phenomena in the field related to empowerment in the Suku Anak Dalam (SAD) settlements, data collection is done by interview, observation, and documentation. Then the data analysis was carried out with qualitative data analysis by collecting data, reducing data, presenting data, and drawing conclusions. Jambi Province is an area that has a large population of Suku Anak Dalam (SAD), one of which is in Sarolangun Regency which is located in the Talang Cheesemat, Limbur Tembesi, Bathin VIII residential area. The Suku Anak Dalam (SAD) community has social problems such as poverty, education, health, and others. The community at this location has been living on a land grant from the church with an area of 1 hectare (Ha), which 19 units of Aid Board Houses from the Indonesian Ministry of Social Affairs have built in 2020. The results of the empowerment program can certainly provide alternative economic sources. As a source of sustainable livelihoods that can meet the daily needs of the Komunitas Adat Terpencil (KAT) residents not only during the social empowerment process, but also to continue to be developed and beneficial for KAT residents. Introducing and providing technical cultivation skills in farming/breeding/gardening and weaving skills as a form of alternative economic business development for KAT residents that can be continuously developed in the long term. This is certainly very necessary to be improved, especially by the government which has duties and responsibilities towards the community.